A patient with severe acute pancreatitis who was successfully rescued by multiple disciplinary teams: a case report. Issue 11 (November 2019) - Zheng, Linhui; Deng, Jun; Long, Xinhua; Zeng, Yuanlin
Severe acute pancreatitis (SAP) is a type of acute abdominal disease. SAP has a high incidence, rapid progression, many complications, high mortality rate (as high as 30%–50%), and is difficult to treat, accounting for approximately 5% to 10% cases of acute pancreatitis. We report diagnosis and treatment of a case of SAP, including a combination of the relevant guidelines and our experience. The patient, who was a 42-year-old woman, was admitted to our hospital after suffering from abdominal pain in the upper abdomen for 1 day. The results of a computed tomography scan in the upper abdomen showed changes in the pancreas accompanied by acute fluid accumulation. The blood amylase level was 1150 U/L. The patient was treated at our Gastroenterology Department for 5.5 months, and received 22 blood transfusions (including red blood cell suspension, plasma, cryoprecipitate, and platelets), four surgical operations, three angiographic interventions, and two times of embolization for hemostasis. We successfully rescued this patient with SAP using minimally invasive, staged, multidisciplinary, and diversified treatment modalities.